Aplikasi Mobile untuk Manajemen Peminjaman Ruang Kelas Studi Kasus Sekolah Bhineka Tunggal Ika - Nicholas Janitra; Nizirwan Anwar (Ikatan Ahli Informatika Indonesia, 2024)
This research aims to design and implement a mobile application for borrowing rooms and classes at a school called